Memorandum on social insurance and allied services in their bearing on neurotic disorder
1943 1943 1940s 19 pages 9 (e) Accidents are sometimes due to the employer's negligence; but when such is clearly the case it is possible for any injured person to recover damages at common law — whether industrial accidents or not. It might be desirable here on purely psychiatric grounds — we are not competent to express an opinion on whether it is legally feasible or proper — to introduce some restrictions on what damages can be collected at common law for any such temporary disability. Restrictions on the possible awards should be defined so that prolongation of temporary illness cannot become a financial advantage to the sufferer, and so that the defendant's responsibility is emphasized as mainly one for treatment and rehabilitation rather than for compensation. (f) Partial temporary disability and training benefit. — It should be in the interests both of the individuals concerned and of the country s [country's] productive capacity to encourage work by any able to engage in it without harm to their disability, even though their disability entitles them to benefits. This requires that as far as reasonably possible they should be allowed to keep whatever they earn, e.g. the social security payment should be subtracted from their earnings as from any pay, but the benefit they are receiving should not be reduced till it would cause the total receipts to exceed 66-90 per cent. (say) of the usual earnings. The limit should not be niggardly, so that there would be a clear benefit in taking such work, but such work should be permitted only after medical approval, and no piece-rates should be permitted while disability benefit is being drawn. Probably for the same reasons training benefit should be at a higher rate than the flat disability or unemployment benefit ; this would enable the final stage of training to include quite a proportion of useful work without causing disgruntlement over "slave-labour," etc. (g) Permanent disability. — To make feasible the administration of pensions on the wide scale that would be necessary under the scheme, it will probably be necessary to draw up a schedule of percentage disability limits for different types of injury to be used as a scale of reference, to reduce the volume of litigation so liable to induce neurosis in cases of partial disability. The question of lump sum payments for permanent disabilities (or other) will be discussed later under workmen's compensation, but it will be assumed for the moment that the basic method will be the weekly payments. There seems no reason for treating blindness separately in this respect — but special problems might well have special departments in the S.S. office for dealing with the difficult treatment and rehabilitation problems which are raised, and these departments should, as suggested for blindness, form liaisons with any existing voluntary organizations. Each type of permanent disability should be considered both from the point of view of the reduction in earning capacity which usually results, and that of the best methods for rehabilitation to maximum usefulness ; the pension should equal the reduction in earning capacity and alter when training alters this (when awarded it should be made conditional on review after training if this is likely to alter it). Such persons should be liable to additional benefits bringing the total income to the flat common benefit rate in the event of temporary illness or unemployment. (h) War service pensions. — These are really a special variety of industrial 292/847/2/174